2015
DOI: 10.1111/vco.12132
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma tissues and cell lines from patients with differing serum alkaline phosphatase concentrations display minimal differences in gene expression patterns

Abstract: Serum alkaline phosphatase (ALP) concentration is a prognostic factor for osteosarcoma in multiple studies, although its biological significance remains incompletely understood. To determine whether gene expression patterns differed in osteosarcoma from patients with differing serum ALP concentrations, microarray analysis was performed on 18 primary osteosarcoma samples and six osteosarcoma cell lines from dogs with normal and increased serum ALP concentration. No differences in gene expression patterns were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(91 reference statements)
1
2
1
Order By: Relevance
“…ALP has been shown to be produced directly by human osteosarcoma cells, and its level can be increased in patients with osteosarcoma 33 . Given the disagreement regarding ALP as a prognostic indicator for osteosarcoma in previous studies, recent studies have reassessed the enzyme as a tumor marker and prognostic predictor, and these rigorous studies have reaffirmed the predictive value of elevated ALP for poor prognosis in patients with osteosarcoma 5,34–36 . In our study, ALP was a predictive factor of good response, but the weight was lower than that of other factors.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…ALP has been shown to be produced directly by human osteosarcoma cells, and its level can be increased in patients with osteosarcoma 33 . Given the disagreement regarding ALP as a prognostic indicator for osteosarcoma in previous studies, recent studies have reassessed the enzyme as a tumor marker and prognostic predictor, and these rigorous studies have reaffirmed the predictive value of elevated ALP for poor prognosis in patients with osteosarcoma 5,34–36 . In our study, ALP was a predictive factor of good response, but the weight was lower than that of other factors.…”
Section: Discussionsupporting
confidence: 53%
“…33 Given the disagreement regarding ALP as a prognostic indicator for osteosarcoma in previous studies, recent studies have reassessed the enzyme as a tumor marker and prognostic predictor, and these rigorous studies have reaffirmed the predictive value of elevated ALP for poor prognosis in patients with osteosarcoma. 5,[34][35][36] In our study, ALP was a predictive factor of good response, but the weight was lower than that of other factors. ALP is generally not considered a prognostic factor for ES and UPS.…”
Section: Clear Bone Boundary Formationcontrasting
confidence: 56%
“…Specifically, OSA cells derived from canine patients with differing serum ALP levels displayed no differences in migration, invasion and chemosensitivity when evaluated in vitro [ 43 ]. Similarly, Rodrigues and colleagues reported that serum ALP is not associated with specific gene expression patterns or intrinsic differences between patient-derived OSA cells [ 44 ]. Yet, different gene expression profiles were shown to be useful in separating canine OSA patients into short and long-term survivors [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent evidence suggests that ALP could merely be a surrogate marker of disease burden [ 53 ] rather than a marker of aggressive biological behavior. This is supported by the similar transcriptional profiles displayed by canine OSA cell lines derived from dogs with low and high ALP [ 54 ]. Our study would then corroborate the lack of prognostic significance of ALP for dogs with similar stages, but further studies are necessary to confirm that.…”
Section: Discussionmentioning
confidence: 76%